The Use of Voice Over To Increasing Students Speaking Skill Trough Description Text - Setiawan, A. Egi; Munir, Munir; Suhesty, Suhesty (Indonesian Journal of Pedagogical and Social Sciences, 2024)
Abstract. The purpose of this study was to discover how students' speaking skills improved via the voice over in terms of two aspects of accuracy: pronunciation and vocabulary. This investigation was conducted in the first grade of SMAN 4 Bulukumba in the province of South Sulawesi, Indonesia. This study's sample included 32 students, 12 male students and 20 female students. The researcher employed a speaking exam to collect data on the progress of students' speaking in terms of two aspects of correctness, namely pronunciation and vocabulary, during the implementation of the voice over. The study was carried out in a single cycle of four meetings. The research findings revealed that implementing a voice over could increase students' speaking abilities. According to the research, the students' mean D-test score was 46.50 in cycle I and improved to 80.30 in cycle II. The improvement rate in speaking ability was 72.70%. It is possible to conclude that incorporating a voice over into the instructional process benefits students' speaking abilities. Keywords: Speaking Skill, Voice Over, Class Action Research